Sensorial Characteristics of Meat of Japanese Quails, Coturnix Coturnix Japonica fed with Ration Containing Snail Meal - Edi Suryanto; Jambari H. Ali; Endang Purwanti (Faculty of Animal Science, Universitas Gadjah Mada, 2000)
Artikel dalam bentuk PDF